Blood biomarkers to distinguish complicated and uncomplicated appendicitis in pediatric patients - Siu-Chung Ha; Ya‐Hui Tsai; Chee-Chee Koh; Shinn‐Gwo Hong; Yun Chen; Chao‐Ling Yao (2024)
/Purpose: Acute appendicitis (AA) stands as the most prevalent cause of acute abdominal pain among children. The potential for morbidity escalates significantly when uncomplicated appendicitis (UA) progresses to complicated appendicitis (CA), which can encompass gangrenous, necrotic, or perforated appendicitis. Consequently, establishing an early and accurate diagnosis of AA, and effectively differentiating CA from UA, becomes paramount. This study explores the diagnostic utility of various blood biomarkers for distinguishing CA from UA in pediatric patients. We conducted a retrospective review of medical records pertaining to pediatric patients who underwent surgery for AA. Patients were categorized as either having UA or CA based on histopathological examination of the appendix. The data collected and analyzed included demographic information, white blood cell (WBC) count, neutrophil proportion, lymphocyte proportion, neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), and C-reactive protein (CRP) levels upon admission. Among the 192 pediatric patients who underwent surgery for AA, 150 were diagnosed with UA, while 42 were diagnosed with CA. The CA group exhibited significantly higher neutrophil proportions, NLRs, PLRs, and CRP levels, alongside lower lymphocyte proportions (all p < 0.01) compared to the UA group. Receiver operating characteristic (ROC) curve analysis disclosed that CRP exhibited the highest specificity, sensitivity, and positive and negative predictive values for predicting CA. CRP emerges as a valuable biomarker for differentiating complicated appendicitis from uncomplicated appendicitis.